Evaluasi Program UKS berdasarkan Model CIPP dalam Implementasi Pelayanan Kesehatan di SDN 163089 Kota Tebing Tinggi - Purba, Fadila Syahrani; Eliska, Eliska; Ashar, Yulia Khairina (Jurnal Biomedika dan Kesehatan, 2025)
Background School-age children are a key group in health development because healthy habits start forming early. However, various national and international surveys show that students still face risks like poor nutrition, smoking, and lack of physical activity. The School Health Unit (UKS) program aims to address these issues through promotive and preventive school-based health services. Methods This study used a qualitative descriptive approach with the CIPP (Context, Input, Process, Product) evaluation model. Data were gathered through observation, in-depth interviews, and document analysis. Informants were chosen through purposive sampling and included the UKS coordinator, school principal, teachers, and students. Data validity was maintained through triangulation of sources and techniques. Results In the Context aspect, there was no formal written policy or established organizational structure for UKS. The Input aspect revealed limited health facilities and the absence of personnel specifically assigned to these facilities. In the Process aspect, only health screening and periodic check-ups were implemented effectively, while other activities, such as health education, Little Doctor training, and nutrition and first aid services, were not conducted according to standards. For the Product aspect, some students demonstrated positive behavioral changes, but these changes were not systematically documented or evaluated. Conclusions The implementation of the UKS program at SD Negeri 163089 Tebing Tinggi City remains symbolic and lacks significant promotive and preventive health efforts. Enhancing the organizational structure, improving health infrastructure, and strengthening intersectoral collaboration are crucial for ensuring the sustainable and effective execution of the program UKS.